Screening of factors affecting the vitamin B12 extraction from Ulva Lactuca by 2-level factorial design - Ruslan, Fatin Shazwani; Darnis, Deny Susanti; Mohammad Noor, Normawaty; Bakhtiar, M. Taher; Aminudin, Nurul Iman (2021)
Abstract Introduction: Ulva lactuca possess many biological properties due to the presence of bioactive compounds. It is believed to be an alternative source for vitamin B12 for strict vegetarians. Methods: The extraction of vitamin B12 was performed using boiling extraction method from freeze-dried (FDB), air-dried (ADB), oven-dried (ODB) and sun-dried (SDB) sample. The effect of solvent:solvent, solute:solvent ratios and pH on total vitamin B12 content extracted from the different dried samples were investigated and analysed using 2-Level Factorial design from RSM. The vitamin B12 (methylcobalamin, hydroxocobalamin, adenosylcobalamin and cyanocobalamin) were analysed quantitatively and qualitatively using HPLC. Results: The retention time (RT) of all samples corresponded to the RT of standard cyanocobalamin (CNCbl), at 1.9 min. ODB sample yielded the highest concentration of CNCbl (0.0210 mg/mL) when extracted at 25:75 % methanol:water, 3 g:60 mL solute:solvent and at pH 3, respectively. The overall model and interaction effect between solvent:solvent ratios and pH, as well as between solvent:solvent and solute:solvent ratios were significant for ODB sample at p-value less than 0.05, scrutinised by ANOVA analysis. Conclusion: Different methods of drying, solvent:solvent, pH and solute:solvent have different effect on the CNCbl content extracted from U. lactuca.